OFC/NFOEC 2008 - 2008 Conference on Optical Fiber Communication/National Fiber Optic Engineers Conference 2008
DOI: 10.1109/ofc.2008.4528699
|View full text |Cite
|
Sign up to set email alerts
|

The First Low-Loss and High-Bandwidth 61-127 Channel Graded-Index Steric Cores Polymer Waveguide

Abstract: We succeeded in fabricating a low-loss and high-bandwidth polymer optical waveguide with graded index type 61-127 cores. The propagation loss is 0.0004 dB/cm at 850 nm and bandwidth of each GI core is 3.2 GHz through 200m waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It has been reported that the data transmission rate required for the high-definition multimedia interface (HDMI) standard (10 Gbps) has been achieved in a system using the double cladding GI POF, even when knotted ten times (Figure 8). Novel POFs with other structures, such as multiple GI cores, are being investigated vigorously all over the world [58].…”
Section: Review Articlementioning
confidence: 99%
“…It has been reported that the data transmission rate required for the high-definition multimedia interface (HDMI) standard (10 Gbps) has been achieved in a system using the double cladding GI POF, even when knotted ten times (Figure 8). Novel POFs with other structures, such as multiple GI cores, are being investigated vigorously all over the world [58].…”
Section: Review Articlementioning
confidence: 99%